The Use of Animated Movie for Teaching Vocabulary: A Pre-experimental Study To The Seventh Grade Students of Madrasah Tsanawiyah Negeri 2 Pontianak In Academic Year 2022/2023 - Pratiwi, Bismi Widya; Gatot Sutapa Yuliana Yohanes; Suhartono Luwandi; Apriliaswati Rahayu; Surmiyati (Kirana Publisher (KNPub), 2023)
This study was conducted to examine the effectiveness of using Animated Movie for teaching vocabulary, especially noun, adjective, and verb to the seventh-grade students of MTsN 2 Pontianak in the academic year 2022/2023 with pre-experimental design as the method. Cluster random sampling was used to select the sample which consisted of thirty-six students. The data was collected by using a multiple-choice test and then analyzed by using the t-test formula. The results indicated that Animated movie increases their vocabulary achievement. The presentation of Animated movie with English subtitles along with the combination of multimedia tools and applications significantly helped the students comprehend the meaning and accurately spell the words. It was proven by the result of the findings of this research that t-test computation at the level of significance of 0.05 with the degree of freedom 35 = 1.689 and the t-value was 9.57 which was higher than the t-table (1.690). The result of the effect size (ES) was 1.56 which was categorized as a strong effect (ES > 1.00). It demonstrated that the alternative hypothesis was accepted and the null hypothesis was rejected. It proved that Animated Movie significantly affects teaching vocabulary.